PENGARUH MODEL PEMBELAJARAN INKUIRI DENGAN METODE PICTORIAL RIDDLE TERHADAP AKTIVITAS BELAJAR GEOGRAFI SISWA SMAN 15 PADANG - Pertiwi, Arizka Ratwo Maida; Novio, Rery (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
Students are less active in the teaching and learning process and less enthusiastic when learning which causes low activity in learning. This study aims to determine the influence of the inquiry learning model with the pictorial riddle method on geography learning activities of SMAN 15 Padang students. This study used a quantitative approach with a pseudo-experimental type. The instruments used are observation sheets and tests. Data collection techniques are carried out by observation and documentation. The results of the t-test analysis obtained a siffinication value of 0.000 < 0.05 and Tcalculate > Ttable, which is 9.089 > 1.6669. The results of the N Gain test of the learning activity of the control class were with a percentage of 22.56% in the ineffective criteria. While the experimental class learning activity with a percentage of 57.59% in the criteria is quite effective. Thus, there is an influence of the use of inquiry models with the pictorial riddle method on students' geography learning activities, because students will be easier to understand the material and can encourage students to be more active in learning so that students can bring out their ideas.